2018
DOI: 10.1371/journal.pone.0204363
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of success rates in eye drop instillation between sitting position and supine position

Abstract: PurposeTo compare the success rates of eye drop instillation in the sitting position and supine position among Japanese patients with ocular diseases (cataract, glaucoma, or retinal and vitreous diseases).MethodsPatients who were hospitalized in Okayama University Hospital for eye surgery were studied. Instillation procedures of each patient in both the sitting and supine positions were recorded using a video camera at the time of instillation. We defined “success” when one drop fell accurately onto the ocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The range of DASH among the currently enrolled patients was 0 to 48, which means that the disturbance of the upper extremities was not severe. Despite this enrollment limitation, DASH examination showed that instillation failure patients had significantly poor or impaired upper limb function, which is consistent with previous reports [ 8 , 11 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The range of DASH among the currently enrolled patients was 0 to 48, which means that the disturbance of the upper extremities was not severe. Despite this enrollment limitation, DASH examination showed that instillation failure patients had significantly poor or impaired upper limb function, which is consistent with previous reports [ 8 , 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, some patients may have difficulty bending their head much more than usual during eye drop instillation because of the decline in their physical performance due to aging. Another option is to adopt a supine position during instillation, as in Naito’s report [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[36][37][38] Patient's age was significantly higher in the (e) Addition-Poor IOP dropout than (a) Addition-Survival group (Table 4). Low compliance with eye drops is age-dependent 39,40 and could have influenced poor IOP control in this study (Table 4). IOP before ripasudil administration in (e) Addition-Poor IOP dropout was significantly higher than (a) Addition-Survival (Table 4).…”
Section: One-year Efficacy Of a Rho Kinase Inhibitor 517mentioning
confidence: 91%